Adverse Biochemical and Physiological Effects of Metformin in Diabetic Type-2 Patients, A Comparative Clinical Study - Rizwana Hussain, Naheed Akhter, Hasan Akbar Khan, Naveed Shuja, Arslan Shuja, Asfand Yar Mujahid, (Pakistan Journal of Medical & Health Sciences, 2022)
Task: The aims and objectives of present study were to highlight the efficacy and adverse side effects of metformin in patients with diabetes type-2 and this study was conducted from December 2021to May 2022 in different medical and diabetic centers of Pakistan. Materials and methods: Subjects: 700 male and female subjects were selected for this study. Division of individuals: 100 normal individuals were in Control group, further 600 individuals were divided into three different groups. In group-X, 200 diabetic type-2, patients were taking 2000 mg/day metformin and in group-Y, 200 diabetic type-2, patients were taking 1500 mg/day metformin while in group-Z, 200 diabetic type-2, patients were taking 500 mg/day metformin respectively. Parameters: Fasting and random serum glucose levels, blood lactic acid levels, serum creatinine levels, myoglobin blood levels and blood hemoglobin levels. Analysis: Microlab and Spectrophotometry kit, regent method were used for the measurement of different parameters. Bio-statistical presentation: All collected raw data were interoperated bio-statistically through the application of SPSS version 2000, in which all parameters were described with the application of standard mean deviation and significant (p<0.05) regression. Results: In this study Fasting and random serum glucose levels, serum creatinine levels, blood lactic acid levels, myoglobin blood levels and blood hemoglobin levels of males and females in Control group, Group-X, Group=Y and Group-Z were (80.1±0.01, 139.2±0.02, 0.2±0.01, 9.2±0.03, 39.2±0.00, 14.1±0.02) (80.1±0.01, 140.2±0.02, 0.1±0.01, 10.2±0.03, 39.2±0.00, 12.1±0.01), (120.1±0.05, 269.2±0.01, 2.2±0.01, 19.1±0.01, 73.2±0.00, 12.1±0.01) (110.1±0.01, 270.2±0.01, 3.2±0.01, 18.1±0.01, 72.2±0.00, 11.1±0.02), (110.1±0.00, 239.2±0.00, 1.2±0.01, 21.1±0.01, 60.2±0.00, 11.1±0.01)( 106.1±0.01, 275.2±0.01, 1.2±0.01, 19.1±0.01, 59.2±0.00, 12.1±0.00) ,( 100.1±0.00, 198.2±0.00, 1.1±0.01, 18.1±0.01,52.2±0.00,12.1±0.00) (110.1±0.00, 239.1±0.00, 1.2±0.01, 17.1±0.00, 51.2±0.00, 12.1±0.00) measured respectively. A remarkable significant (p<0.05) were seen in between the variables of each group. Conclusion: Metformin considered as a safe drug for diabetic type-2 patients but it has some very severe side effects, it may cause lactic acidosis, protein breakdown, skeletal muscular atrophy and striking loss of muscle etc. Long life its use can develop myocardial infarction.